Long-term outcome in acute myelogenous leukemia autografted with mafosfamide-purged marrow in a single institution: adverse events and incidence of secondary myelodysplasia - Abdallah Khalafallah, Alhossain; Egerer, Gerlinde; Weber-Nordt, Renate; Körbling, M.; Haas, Rainer; Ho, Anthony Dick (Bone marrow transplantation, 2002)
We have analyzed the long-term outcome and toxicities in 98 patients with high-risk acute myelogenous leukemia (AML) who were treated with autologous bone marrow transplantation (ABMT) and monitored for a median observation period of 11.67 years. Between 1983 and 1994, 98 patients in our institution in first or second and higher complete remission (CR) underwent total body irradiation and high-dose cyclophosphamide prior to ABMT purged with mafosfamide. Twenty-seven out of the 90 evaluable patients (30%) were alive and in continuous CR for a median of 11.67 years (range, 6.39-15.53) after ABMT and could be considered as ‘cured’. Among the 90 patients, 39 were transplanted at first CR and had a significantly higher survival rate than those transplanted at ⩾2 CR. Younger patients (<40 years) had a better prognosis and patients with FAB M1-4 had a more favorable outcome than those with M5. Long-term complications included four patients with cardiac complications, two with renal insufficiency. Five developed HCV infections, four myelodysplastic syndrome. The incidence of cataract among the long-term survivors was 44.4%. Therefore, a significant number of adult patients with AML in first CR derived long-term benefit from ABMT, despite the risks of a few long-term complications and of MDS (4.4%).
Gesehen am 14.12.2021